Establishing a Reproducible Hypertrophic Scar following Thermal Injury: A Porcine Model. Issue 2 (February 2015) - Rapp, Scott J.; Rumberg, Aaron; Visscher, Marty; Billmire, David A.; Schwentker, Ann S.; Pan, Brian S.
Abstract : Background: Our complete understanding of hypertrophic scarring is still deficient, as portrayed by the poor clinical outcomes when treating them. To address the need for alternative treatment strategies, we assess the swine animal burn model as an initial approach for immature scar evaluation and therapeutic application. Methods: Thermal contact burns were created on the dorsum of 3 domestic swine with the use of a branding iron at 170°F for 20 seconds. Deep partial-thickness burns were cared for with absorptive dressings over 10 weeks and wounds evaluated with laser and negative pressure transduction, histology, photographic analysis, and RNA isolation. Results: Overall average stiffness (mm Hg/mm) increased and elasticity (mm) decreased in the scars from the initial burn injury to 8 weeks when compared with normal skin ( P < 0.01). Scars were thicker, more erythematous, and uniform in the caudal dorsum. The percent change of erythema in wounds increased from weeks 6 to 10. Histology demonstrated loss of dermal papillae, increased myofibroblast presence, vertically oriented vessels, epidermal and dermal hypercellularity, and parallel-layered collagen deposition. Immature scars remained elevated at 10 weeks, and minimal RNA was able to be isolated from the tissue. Conclusions: Deep partial-thickness thermal injury to the back of domestic swine produces an immature hypertrophic scar by 10 weeks following burn with thickness appearing to coincide with the location along the dorsal axis. With minimal pig to pig variation, we describe our technique to provide a testable immature scar model.